Кралюк П. Шестиднев, або Корона дому Острозького: Роман - Дзюба, С. (Сiверянський лiтопис, 2011)
Рецензія на книгу: Кралюк П. Шестиднев, або Корона дому Острозького: Роман. – К. : Ярославів Вал, 2010. – 320 с.